Uveitis in dogs infected with Ehrlichia canis - Oriá, Arianne Pontes [UNESP]; Pereira, Patrícia Mendes [UNESP]; Laus, José Luiz [UNESP] (Universidade Federal de Santa Maria, 2004)
Uveitis is a common disease in dogs with a multitude of causes, one of them being ehrlichiosis. This article reviews several uveitis etiologies, as well as the important aspects of canine ehrlichiosis, including its diagnosis and the main ophthalmic signs presented in these cases. It also reports the therapy that should be used.

As uveítes, que se constituem em oftalmopatias comuns entre os cães, decorrem de inúmeras causas. Em nosso meio, destaca-se a erliquiose. Este artigo discute as várias causas da enfermidade ocular, bem como aspectos importantes da enfermidade parasitária, incluindo os sinais, o diagnóstico e o tratamento.
Uveíte em cães infectados com Ehrlichia canis
Keywords: canine; chorioretinitis; hyphema; uveitis; Ehrlichia canis; canino; corioretinite; hifema; uveíte; Ehrlichia canis